Finished Product Warehouse Layout Design Using Shared Storage Method - Juliani Febiyanti (IHSA Institute, 2020)
PT. XYZ is a private company engaged in the business of producing ceramics. The problem in the current warehouse is the presence of defective ceramic products due to irregular placement of finished products. Irregular placement of ceramic products, which can cause inefficiency in picking time and make it difficult for workers because of the limited space for movement that can hinder the movement of workers on the production floor. The above problems can be overcome by using the Shared storage method where goods are placed in the storage area closest to the entrance-exit (I/O) door. This method would be better used in types of factories that have the same product dimensions or not much different. The lack of good procedures for arranging goods in the warehouse causes problems in the warehouse, so that the warehouse seems cramped and less organized. The condition of the warehouse layout that is not based on a comprehensive layout design can lead to inefficiency in the time of taking and storing materials and making it difficult for operators to handle materials due to warehouse limitations. In this case, the process of placing goods in the warehouse at the ceramic factory of PT. XYZ will be arranged to reduce the forklift movement distance shorter which can be seen from the results of the proposed design on the layout of the finished product placement in the warehouse. Looking at the design of the proposed ceramic product warehouse layout, the percentage of total travel distance savings in the finished product warehouse is 37.76%.